ASPEK HUKUM DAN PRAKTIK LABELISASI HALAL PRODUK MAKANAN DI INDONESIA DAN PAKISTAN: SEBUAH KAJIAN KOMPARATIF: Legal Aspects and Practices of Halal Labeling of Food Products in Indonesia and Pakistan: A Comparative Study - Muhammad Fathan Mustaqiem; Siti Nurbaiti (Reformasi Hukum Trisakti, 2026)
This study conducts a comparative analysis of the legal aspects and practices of halal food labeling in Indonesia and Pakistan, with the world's largest Muslim demographic (248.22 million out of Indonesia's 284.97 million population as of 2024). The problem statement is how food product labeling is regulated in Indonesia and Pakistan and how food labeling regulations are implemented and enforced in both countries. The research method applied was normative legal research. The results show that Indonesia is strong normatively (das sollen) through the integration of religion and law, but weak in execution (das sein) due to complex coordination and cases such as Ayam Goreng Widuran; Pakistan excels in consistency of sanctions (90% urban compliance) through PHA audits. The rechtsvergleichung discussion highlights the efficiency of Pakistan's single model versus Indonesia's hybrid model, with similarities in non-commercial consumer protection. The conclusion recommends reforms in Indonesia: integrated authorities, strict sanctions, and digitization to align das sollen-das sein and increase global halal competitiveness.